Multi-lane trajectory control for autonomous vehicle convoy based on a longitudinal and lateral control coupled approach. (23rd March 2022) - Mohamed-Ahmed, M-M.; Naamane, Aziz
In this paper, we propose two control approaches for the vehicle convoy in multi-lane trajectories (three lanes i, j, k ) with two different configurations. The first approach decouples the controls, while the second approach couples the longitudinal control with the lateral variations between two neighbouring lanes. The lateral movement uses different control laws (linearisation control by inverse dynamic, first order FOSM and second order sliding mode control SOSM) for each lane to compare these different controllers. The results show the performance of the second approach against the convoy concept. These different controllers ensured trajectory tracking even in the presence of errors in the model parameters. The lateral deviation remains acceptable in the case of parameter estimation errors for these different controllers. The validation has been carried using SCANeR ™ -Studio and MATLAB Simulink for a convoy of ten vehicles.